Protocol for managing acute cancrum oris in children: An experience in five cases - Adeola D; Obiadazie A (Wolters Kluwer Medknow Publications, 2009)
Background: Acute cancrum oris (NOMA) is a major health concern in most parts of northern Nigeria, affecting children aged 2-9 years. The management of the acute phase/condition poses a great clinical challenge. We present our protocol for the management of acute NOMA in a referral health facility in northern Nigeria. Materials and Methods: The management of five consecutive children with acute NOMA managed at the maxillo-facial department of Ahamdu Bello University Teaching Hospital, Kaduna, is presented. The initial management is conservative, followed later by multiple reconstructions. Results: NOMA thrives in children with poor nutritional status and/or compromised immune status. Aggressive wound debridement, antibiotic therapy and nutritional rehabilitation limited the spread of the orofacial tissue destruction and produced rapid wound healing. Conclusion : The management of acute NOMA should be nonoperative; surgery is only indicated to debride the ulcer. Efforts to boost patient′s immune and nutritional status limit further tissue destruction and produced satisfactory wound healing.